Is the Revenue Diversification Strategy in Sharia Banks Effective during Covid-19 Pandemic? - Rizkiana Iskandar; Dian Urna Fasihat (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This research aims to examine the role of revenue diversification in ensuring financial performance remains stable and various risks in Islamic banks can be mitigated. Methodology/approach: This type of research is quantitative and uses purposive sampling on the Islamic banking statistical report published by the Financial Services Authority (OJK) on March 2021 to June 2023. The data will be tested using multiple linear regression analysis using SPSS version 21. Findings: The results of the study indicate that the diversification strategy implemented by Sharia Banks in Indonesia can improve financial performance as proxied by ROA and ROE, and can reduce financing risk as proxied by NPF. Practical implications: The results of this study are expected to provide recommendations for Islamic banking in determining various non-operational activity policies to maximize income in various conditions, including during the COVID-19 pandemic. Originality/value: This study tries to see the effect of income diversification strategy by increasing non-operational income that can be done as an effort to maintain the financial stability of Islamic banks in any condition. In addition, the researcher added control variables in the form of total assets, capital, FDR, and the Sharia Supervisory Board (DPS) to strengthen the research results.